A PCE plume discharging to a river, investigations of flux, geochemistry, and biodegradation in the streambed - Conant, Brewster (University of Waterloo, 2001)
A tetrachloroethene (PCE) groundwater plume emanates from beneath a dry cleaner facility and discharges to a 60 m-long reach of the Pine River in Angus, Ontario, Canada. The streambed and near-stream zone were shown to be a dynamic and unique environment that modified the distribution, concentration, and composition of the plume. The plume and hydrogeology were characterized using a Waterloo Profiler, mini-profilers, bundle multilevel samplers, driveable multilevel samplers, Ground Penetrating Radar surveys (of the streambed), streambed temperature mapping (to identify discharge zones), drivepoints, and sediment coring. Low hydraulic conductivity silt, clay, and peat deposits underlying the sandy streambed deposits caused the plume to discharge over a large area of the streambed and extend across the full width (11 to 14 m) of the river at some locations. Spatial variations in the geology resulted in groundwater fluxes that varied from 0.03 to at least 446 L/m^2d. Although no appreciable biodegradation of the plume occurred in the upgradient aquifer, anaerobic biodegradation in the top 2.5 m of the streambed dramatically altered the plume composition by transforming PCE primarily to cis-1,2-dichloroethene (cDCE) and vinyl chloride (VC) and to a lesser extent trichloroethene (TCE), 1,1-dichloroethene (cDCE) and vinyl chloride (VC) and to a lesser extent trichloroethene (TCE), 1,1-dichloroethene (11DCE), trans-1,2-dichloroethene (tDCE), ethene, and ethane. The degree of biodegradation was spatially variable at a depth of 0.3 m in the streambed, but overall, the streambed reduced the total mass of PCE discharging to the river by 54 to 59% resulting in large accumulations of chlorinated degradation products and no appreciable mineralization. The high concentrations of volatile organic compounds (VOCs) that remained represented a potential hazard to benthic and hyporheic aquatic life. The VOC concentrations were spatially variable, with up to 5529 ug/L found at one location and no VOCs detected 3.5 m away, while at another location, 3639 ug/L of PCE was reduced to 125 ug/L and almost completely transformed to cDCE over a vertical distance of only 0.15 m. Transformations of PCE generally occurred over relatively short vertical distances (< 0.45 m) and was associated with sharp changes in redox conditions. The degree of biodegradation was highly correlated with the redox conditions and the magnitude of fluxes because the low hydraulic conductivity deposits that caused the low fluxes were also organic-rich and strongly reducing. High amounts of dechlorination (i.e. production of ethene and ethane) occurred when fluxes were very low and sulfate reducing to methanogenic conditions existed. Virtually no biodegradation occurred in high flux areas where water was anaerobic to nitrate reducing. A new method of calculating groundwater fluxes based on streambed temperature measurements and testing of mini-piezometers was developed and used to create a conceptual flow model that was based on the magnitude and direction of the fluxes. Five types of flow behavior were identified: 1) short-circuits and springs, 2) high discharge, 3) low to moderate discharge, 4) no discharge and 5) recharge. This flow model provided a valuable framework for interpreting and characterizing the complex patterns of redox conditions, biodegradation, and mass discharges. Despite high VOC concentrations in the streambed, an estimated 24.9x10^3 L/d of contaminated groundwater flowing to the river, and an estimated total mass of 3.2 to 4.0 g/d of PCE and 2.8 to 4.2 g/d of cDCE discharging to the river, VOCs were rarely detected in surface water (summer river flows were typically 1.4 to 2 m^3/s). PCE was detected at concentrations <_ 3.1 ug/L and on one occasion was as high as 23.2 ug/L whereas no cDCE or VC was detected in surface water. This occasional detection of PCE may have occurred because PCE was associated with high groundwater discharge zones whereas cDCE was associated with low groundwater discharges. I n general, high VOC concentrations in the streambed were no associated with the high groundwater discharge zones. This study demonstrates the complex interaction of hydrogeologic, geochemical, and biochemical processes that occur in streambeds and the resulting fine scale spatial variability in plume discharge.
Keywords: Harvested from Collections Canada